2015
DOI: 10.48550/arxiv.1504.08030
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pseudo-ballistic transport in 3D topological insulator quantum wires

Joseph Dufouleur,
Louis Veyrat,
Emmanouil Xypakis
et al.

Abstract: Quantum conductance fluctuations are investigated in disordered 3D topological insulator quantum wires. Both experiments and theory reveal a new transport regime in a mesoscopic conductor, pseudo-ballistic transport, for which ballistic properties persist beyond the transport mean free path, characteristic of diffusive transport. It results in non-universal conductance fluctuations due to quasi-1D surface modes, as observed in long and narrow Bi2Se3 nanoribbons. Spin helical Dirac fermions in quantum wires ret… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…Our finding of AB oscillations in the diffusive regime confirmed and extended a recent experiment which found an AB signal in quite long wires as long as the perimeter P < l is less than than the scattering length l. 23 We found that if P < l the AB signal depends periodically on E F , and if P > l its amplitude is random. Our observation of AAS oscillations in the ballistic regime verifies theoretical work showing that they can occur even in ballistic samples as a consequence of constructive quantum interference between time-reversed circuits around the wire.…”
Section: Magnetic Phase Effects In Wiressupporting
confidence: 90%
“…Our finding of AB oscillations in the diffusive regime confirmed and extended a recent experiment which found an AB signal in quite long wires as long as the perimeter P < l is less than than the scattering length l. 23 We found that if P < l the AB signal depends periodically on E F , and if P > l its amplitude is random. Our observation of AAS oscillations in the ballistic regime verifies theoretical work showing that they can occur even in ballistic samples as a consequence of constructive quantum interference between time-reversed circuits around the wire.…”
Section: Magnetic Phase Effects In Wiressupporting
confidence: 90%
“…Our finding of AB oscillations in the diffusive regime confirm and extend a recent experiment which found an AB signal in quite long wires as long as the perimeter P < l is less than than the scattering length l. 18 We find that if P < l the AB signal depends periodically on E F , and if P > l its amplitude is random. Our observation of AAS oscillations verifies theoretical work showing that they occur in the ballistic regime as a consequence of constructive quantum interference between time-reversed circuits around the wire.…”
supporting
confidence: 90%
“…One may distinguish between Aharonov-Bohm oscillations with period Φ 0 and Altshuler-Aronov-Spivak (AAS) oscillations with period Φ 0 /2. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In addition Universal Conductance Fluctuations (UCFs) are observed -a noise-like component of G(Φ) which depends sensitively on the Fermi level and on disorder. 5,9,[24][25][26][27][28][29][30] TIs also host a Perfectly Conducting Channel (PCC)a conductance quantum which is remarkable for its persistence in very long TI wires, its topological protection, and its status as a 3-D analogue of the quantum Hall effect.…”
mentioning
confidence: 99%
“…Studying the TSS then requires to identify the their own contribution to charge transport. In Bi 2 Se 3 nanostructures, this was proved possible by studying quantum transport: Aharonov-Bohm effect 7,8 , Conductance Fluctuations 9 , and Shubnikov-de-Haas oscillations (SdHO) 2,[10][11][12][13][14][15][16][17][18][19] . So far, the analysis of SdHO in Bi 2 Se 3 remains unclear.…”
mentioning
confidence: 99%